Status of spontaneous reporting of adverse drug reaction by physicians in Delhi - P, Amrita; SP, Singh (Indian Journal of Pharmacy Practice)
Adverse drug reaction (ADR) monitoring and reporting activity is in its infancy in India. Physicians being frontline caregivers, a study was conducted to determine the level of awareness of physicians about ADR reporting and the extent of their involvement in pharmacovigilance activities. A study of physicians was conducted among various government hospitals, private hospitals and private clinics of Delhi (INDIA) from Dec 2009 to July 2010. A questionnaire containing 19 questions was distributed to 200 physicians. Only 124 physicians completed the questionnaire giving response rate of 62%. Out of these, only 70.97% physicians were aware of the term Pharmacovigilance. Majority of the respondents (99.19%) consider ADR monitoring to be essential. However, 96.77% physicians noticed ADRs in patients but only 34.68% physicians reported them. Only 8.87% of the physicians knew the pharmacovigilance centers of Delhi. Out of these only 2.42% had phone number and address of these centers and they reported ADRs at these centers. The major reasons for not reporting ADR were: not aware of reporting centers (97.58%), non-availability of ADR reporting form (90.32%), adverse drug reaction already well known (57.26%), uncertainty about drug causing it (47.58%) and lack of set procedure of ADR reporting in their organization (42.74%). Most of physicians (87.90%) consider ADR monitoring should be made mandatory on doctors. Despite good observation and knowledge of ADR among doctors the rate of reporting to ADR monitoring centers is very low.
Keywords: ADR; ADR reporting; Pharmacovigilance; Physicians